The Role Of Internal Audit In Fraud Prevention And Disclosure : Literature Riview - Khairini Melinda; Ariama Susanti; Juneva Kastarina Tarigan; Deliana Deliana; Ilham Hidayah Napitupulu (Universitas Islam Bandung, 2022)
This study aims to determine the effect of internal audit in preventing and disclosing fraud. The number of frauds that occur in an organization shows the need for an internal audit body in the company so that it can reduce or even eliminate fraud that occurs. This literature review is a study of the role of internal audit in preventing and disclosing fraud which aims to find out the variables in internal audit for preventing and disclosing fraud based onprevious studies, so there is still a lotof potential forfurthermodification/development. Of the ten studies included in this literature review, there are differences in research results. Eight studies state that internal audit has a significant effect on preventing and disclosing fraud, but two articles state that internal audit does not have a significant effect on preventing and disclosing fraud.